2018
DOI: 10.1016/j.chemosphere.2018.03.110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glyphosate and its commercial formulation, Roundup® Ultramax, on liver histology of tadpoles of the neotropical frog, Leptodactylus latrans (amphibia: Anura)

Abstract: In the last years, the agricultural expansion has led to an increased use of pesticides, with glyphosate as the most widely used worldwide. This is also the situation in Argentina, where glyphosate formulations are the most commercialized herbicides. It is known that glyphosate formulations are much more toxic than the active ingredient, and this difference in toxicity can be attributed to the adjuvants present in the formula. In this context, the aim of the present study was to evaluate and compare sub-lethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 83 publications
2
21
0
3
Order By: Relevance
“…Changes in the amount of melanin was found in frogs experimentally exposed to several xenobiotics. In these experiments, the variation in melanin was due to several compounds (reviewed in De Oliveira et al (2017)), such as polycyclic aromatic hydrocarbons (PAHs;Fanali et al, 2018), herbicides (e.g., atrazine and glyphosate; Pérez-Iglesias et al, 2019;Bach et al, 2018), drugs, and endocrine disrupters (Gregorio et al, 2016). Here, we found large amounts of atrazine in the area under agriculture influence (more than 5,000 times the limit accepted by Brazilian legislation, i.e., 5,349.940 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the amount of melanin was found in frogs experimentally exposed to several xenobiotics. In these experiments, the variation in melanin was due to several compounds (reviewed in De Oliveira et al (2017)), such as polycyclic aromatic hydrocarbons (PAHs;Fanali et al, 2018), herbicides (e.g., atrazine and glyphosate; Pérez-Iglesias et al, 2019;Bach et al, 2018), drugs, and endocrine disrupters (Gregorio et al, 2016). Here, we found large amounts of atrazine in the area under agriculture influence (more than 5,000 times the limit accepted by Brazilian legislation, i.e., 5,349.940 µg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Teratogenic effects were reported in a treefrog (Scinax nasicus) (Lajmanovich et al, 2003) and in the embryo of the African clawed frog (Xenopus laevis) (Paganelli et al, 2010) in response to exposure to Glyfos R or Roundup Classic R at levels corresponding to 3-7.5 and 96-160 mg/l glyphosate concentrations, respectively. Hepatotoxicity of glyphosate and Roundup Ultramax R was observed in tadpoles of the neotropical frog Leptodactylus latrans (Bach et al, 2018), but the formulated herbicide product was found 10-fold more toxic than glyphosate, leading to histopathologic lesions at a level corresponding to a glyphosate concentration of 0.37 mg/l. Teratogenicity is not exclusively related to POEA, as a POEAfree micro-emulsion formulation containing polyethoxylated isotridecyletherpropylamine as a surfactant, Roundup R Power 2.0 has been found to exert embryotoxicty on X. laevis in the frog embryo teratogenesis assay-Xenopus (FETAX) with a 96-h EC 50 value of 7.8 mg/l, while glyphosate was not found to be embryolethal, only causing edemas at the highest concentration tested, 50 mg/l (Bonfanti et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Changes in the amount of melanin was found in frogs experimentally exposed to several xenobiotics. In these experiments, the variation in melanin was due to several compounds (reviewed in De Oliveira et al 2017), such as polycyclic aromatic hydrocarbons (PAHs; Fanali et al 2018), herbicides (e.g., atrazine and glyphosate; Pérez-Iglesias et al 2019;Bach et al 2018), drugs, and endocrine disrupters (Gregorio et al 2016). Here, we found large amounts of atrazine in the area under agriculture influence (more than 5,000 time the limit accepted by Brazilian legislation, i.e.…”
Section: Discussionmentioning
confidence: 99%